2013
DOI: 10.1371/journal.pone.0062016
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Human Macrophages to β-Glucans Depends on the Inflammatory Milieu

Abstract: Backgroundβ-glucans are fungal cell wall components that bind to the C-type lectin-like receptor dectin-1. Polymorphisms of dectin-1 gene are associated with susceptibility to invasive fungal infection and medically refractory ulcerative colitis. The purpose of this study has been addressing the response of human macrophages to β-glucans under different conditions mimicking the composition of the inflammatory milieu in view of the wide plasticity and large range of phenotypical changes showed by these cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
5
23
0
1
Order By: Relevance
“…Macrophages cultured in the presence of human serum show a high sensitivity to LPS as judged from a rapid induction of COX-2 and a high production of PGE 2 . In contrast, particulate zymosan, an extract of the Saccharomyces cerevisiae cell wall mainly composed of b-glucans, only induces COX-2 expression several hours after particle uptake (Municio et al, 2013). This putative phagolysosomal route of PGE 2 production is synergistically enhanced by low concentrations of LPS, which agrees with the results observed with crystal-like materials (Kuroda et al, 2011).…”
Section: The Plasticity Of Mononuclear Phagocytes Explains Distinct Psupporting
confidence: 87%
See 1 more Smart Citation
“…Macrophages cultured in the presence of human serum show a high sensitivity to LPS as judged from a rapid induction of COX-2 and a high production of PGE 2 . In contrast, particulate zymosan, an extract of the Saccharomyces cerevisiae cell wall mainly composed of b-glucans, only induces COX-2 expression several hours after particle uptake (Municio et al, 2013). This putative phagolysosomal route of PGE 2 production is synergistically enhanced by low concentrations of LPS, which agrees with the results observed with crystal-like materials (Kuroda et al, 2011).…”
Section: The Plasticity Of Mononuclear Phagocytes Explains Distinct Psupporting
confidence: 87%
“…Attempts to correlate the state of macrophage differentiation with eicosanoid release have steadily shown a predominant production of PGE 2 and PGD 2 and a varying pattern of response dependent on the presence of costimulatory substances. For instance, growth factors such as macrophase colony-stimulating factor and granulocyte macrophage colony-stimulating factor elicit profound changes on the expression of receptors such as DC-SIGN and the dectin-1 B isoform, that is, the isoform displaying the most efficient productive binding to b-glucans (Rosas et al, 2008;Municio et al, 2013). Macrophages cultured in the presence of human serum show a high sensitivity to LPS as judged from a rapid induction of COX-2 and a high production of PGE 2 .…”
Section: The Plasticity Of Mononuclear Phagocytes Explains Distinct Pmentioning
confidence: 99%
“…This supports the endotoxin-BG synergy observed in several previous studies [19,28]. However, BG alone could not induce macrophage cytokine production in either FcGRIIb-/-or wild-type mice, sug- gesting a limited independent proinflammatory potential [29,30]. The main pattern recognition receptors responsible for the detection of endotoxin and BG are TLR-4 and dectin-1, respectively [31].…”
Section: The Influence Of Impaired Gi Barrier and Gut Translocation Osupporting
confidence: 84%
“…We do not know why the two cell types had different requirements for Dectin-2, but others have shown that mouse bone marrow-derived macrophages and BMDC react differently to Dectin-1 agonists because macrophages and BCs are reprogrammed by cytokines used as in vitro growth factors (75). Municio et al recently showed that human macrophages and DCs responded differently to zymosan and ␤-glucan depending on whether or not M-CSF was used to mature the cells or if TLR ligands or IFN-␥ were added to the reaction mixture (76). In our in vitro assays with BMDC, we did not detect IL-12p70 or IFN-␥, perhaps because we were studying genetically susceptible B6 mice, which do not generate Th1 immune responses to this infection (20,77).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo spherules have an outer membrane made up of membranous glycoprotein (SOWgp) (87) that can be lost during in vitro cultivation, and SOWgp could interact with other receptors or prevent recognition by CLR of mannose ligands in the cell wall. In addition, we used FKS that were too large to be ingested and so probably did not interact with intracellular TLRs that influence the way macrophages and DCs respond to zymosan (76). Since a decrease in cytokine production by Dectin-1 Ϫ/Ϫ macrophages and BMDC in vivo does predict greater susceptibility to infection (23), we can only conclude that in vitro results may not predict susceptibility, which needs to be determined in vivo.…”
Section: Discussionmentioning
confidence: 99%